The magic school bus. Season one [videorecording (DVD)] (distributed by Cinedigm Entertainment, 2015)
Watch as Ms. Frizzle and the gang journey inside the human body, get swept up in a tornado and bravely visit a bee's nest. Relive your favorite episodes from the season that started it all.